Between Past and Future - 2/1
Recording of the international conference "Between Past and Future: The Revolutions of 1989 and the Struggle for Democracy in Central and Eastern Europe" organized by CEU and the University of Maryland, held at CEU between 26th and 28th of March, 1999. Contains the inaugural session of the conference which is presented by CEU Professor Sorin Antohi and the introductory remarks which are delivered by President and Rector of CEU Josef Jařab and the Mayor of Budapest Gábor Demszky. Contains also the recording of the press conference and the Q&A session taking place on the first day of the international conference where the speakers are Professor Sorin Antohi (Academic Pro-Rector at CEU), Professor Vladimir Tismăneanu (Maryland University) and Dr. István Teplán (Executive Vice-President of CEU).